Meningkatkan Daya Saing Industri Komponen Otomotif Melalui Sinergi Penelitian - Murwanto, Tri Agus (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
machetes, knives, garden scissors, cookie cutters, rim of wheel, flywheel, components of machinenJ,pumps dragon, Jait Wat brake blocks, components oj electrical machines and others. Cost IndustrWlMetal (UK) Tegal in Central Java Province, the mwt advanced when compared with other castingindustnj in Indonesia bemuse is can contribute 22.69% of its gross income. Through our researchactivities of DIPA in the financial year of 1990/1991, 1992/1-993 the automotive Deputy IPT UPI.Research Telimek has conducted research activities in synergiJ with Cast Metal Industries (UK)Tegal1 in the form of metal casting for the manufacture, of engine blocks. The research is expected tohave a positive impact for both parties, while R dan D can contnbute to the. problems faring theindustn;, because the innovation-innovation are taken as benefit, while for the industnj with innovationsin R dan D, the results is expected to increase the competitiveness of its products.